2015
DOI: 10.15171/ijhpm.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

Discussing the Effects of Poor Health Literacy on Patients Facing HIV: A Narrative Literature Review

Abstract: Background: Scholars describe poor health literacy as a "silent epidemic, " which is challenging the functioning of healthcare systems all over the world. Health literacy is mainly meant as an individual trait which concerns the ability to obtain, process, and understand basic health information in order to effectively navigate the health system. Low health literate patients perceive poor self-efficacy dealing with their health conditions, are not willing to be involved in the provision of care, show larger ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 89 publications
4
43
0
Order By: Relevance
“…Health literacy was associated with a poorer response to cART in bivariate analysis, but the association was no longer significant after adjustment. However, our indicator of health literacy only took into account the patients' knowledge of CD4 + T-cell count and viral load evolution during treatment, which is only one of all the health literacy dimensions, and can be measured with specific tools [48][49][50]. We did not find an association with depression, even though such an association has been largely reported in the literature [7,51].…”
Section: Discussionmentioning
confidence: 71%
“…Health literacy was associated with a poorer response to cART in bivariate analysis, but the association was no longer significant after adjustment. However, our indicator of health literacy only took into account the patients' knowledge of CD4 + T-cell count and viral load evolution during treatment, which is only one of all the health literacy dimensions, and can be measured with specific tools [48][49][50]. We did not find an association with depression, even though such an association has been largely reported in the literature [7,51].…”
Section: Discussionmentioning
confidence: 71%
“…However, Rachlis et al [40] have shown in a systematic review of studies in LMICs that higher education was associated with good adherence. A lower level of general education and poorer literacy may impact negatively on some patients' ability to adhere, while a higher level of education has a positive impact [41].…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which health literacy influences HIV testing behavior is currently unclear, but other data have shown that higher health literacy is associated with better HIV-related health behaviors and outcomes. For instance, one study found that educational attainment of high school or less is associated with decreased testing frequency (24), and among people who already have a diagnosis of HIV, there is some evidence of increased medication adherence and improved outcomes among people with higher levels of health literacy (25, 26). However, additional data suggest that low health literacy may facilitate testing.…”
Section: Discussionmentioning
confidence: 99%